Assessing Knowledge, Attitudes and Readiness of Nurses Regarding Patients’ Sexual Health Problems - Jadoon, Shaista Bibi; Nasir, Summaira; Victor, Gideon; Pienaar, Abel Jacobus; Nasir, Fizza (2023)
Sexual health is fundamental to the physical, psychological and spiritual well-being of a human, couple, and family; it is the social and economic development of modern societies and civilized nations (WHO, 2020). The ability of human sexual health and well-being depends upon their sufficient knowledge, risky sexual behaviors, vulnerability to the adverse consequences, and good quality of sexual health care and beneficial environment; it can promote and sustains human sexual health (WHO, 2020). Sexual health is an international human right; it is the responsibility of the national government to ensure sexual health rights and policies for all individuals, communities and families (Gruskin et al., 2019).The stigmatizing and discriminating attitudes of health care workers need to change to reduce patients refusal to seeking sexual health services (UNAIDS, 2020). The purpose of this review was assessing the Knowledge, attitudes and readiness of nurses regarding patients’ sexual health problems. The PRISMA guidelines were used for conducting this literature review. The full text articles were searched from Cochrane, Pub-Med, and Cumulative Index to Nursing Allied Health Literature and Google Scholar. The relevant keywords were used including sexuality, sexual health, nursing students, nurses, doctors, physicians, consultants, sexual health policies, sexual health training and education, and sexual health barriers. Knowledge and training, attitudes of healthcare professionals, the corresponding factors included ineffective communication, social stigma, taboo, gender, culture, inadequate institutional policies, and faculty role-modelling. The healthcare professionals should respect patients’ sexual health problems. There should be proper training for the nursing teachers and students to deal with sexual health problems. The faculty clinical role modeling should encourage on clinical for students learning regarding patients sexual health problems. The component of patients’ sexual health should be included in the nursing curricula in Pakistan. There should be a longitudinal on patients’ sexual health problems.